Minimally Invasive Tissue Sampling: A Tool to Guide Efforts to Reduce AIDS-Related Mortality in Resource-Limited Settings. (15th December 2021) - Letang, Emilio; Rakislova, Natalia; Martinez, Miguel J; Carlos Hurtado, Juan; Carrilho, Carla; Bene, Rosa; Mandomando, Inacio; Quintó, Llorenç; Nhampossa, Tacilta; Chicamba, Valéria; Luis, Elvira; Ismail, Mamudo R; et al.
Abstract: Background: Available information on the causes of death among people living with human immunodeficiency virus (PLHIV) in low- and middle-income countries (LMICs) remains scarce. We aimed to provide data on causes of death in PLHIV from two LMICs, Brazil and Mozambique, to assess the impact of clinical misdiagnosis on mortality rates and to evaluate the accuracy of minimally invasive tissue sampling (MITS) in determining the cause of death in PLHIV. Methods: We performed coupled MITS and complete autopsy on 164 deceased PLHIV (18 children, 36 maternal deaths, and 110 adults). HIV antibody levels and HIV RNA viral loads were determined from postmortem serum samples. Results: Tuberculosis (22.7%), toxoplasmosis (13.9%), bacterial infections (13.9%), and cryptococcosis (10.9%) were the leading causes of death in adults. In maternal deaths, tuberculosis (13.9%), bacterial infections (13.9%), cryptococcosis (11.1%), and cerebral malaria (8.3%) were the most frequent infections, whereas viral infections, particularly cytomegalovirus (38.9%), bacterial infections (27.8%), pneumocystosis (11.1%), and HIV-associated malignant neoplasms (11.1%) were the leading cause among children. Agreement between the MITS and the complete autopsy was 100% in children, 91% in adults, and 78% in maternal deaths. The MITS correctly identified the microorganism causing death in 89% of cases. Conclusions: Postmortem studies provide highly granular data on the causes of death in PLHIV. The inaccuracy of clinical diagnosis may play a significant role in the high mortality rates observed among PLHIV in LMICs. MITS might be helpful in monitoring the causes of death in PLHIV and in highlighting the gaps in the management of the infections.